2016
DOI: 10.1002/eji.201445388
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering CD137 (4‐1BB) signaling in T‐cell costimulation for translation into successful cancer immunotherapy

Abstract: CD137 (4-1BB, TNF-receptor superfamily 9) is a surface glycoprotein of the TNFR family which can be induced on a variety of leukocyte subsets. On T and NK cells, CD137 is expressed following activation and, if ligated by its natural ligand (CD137L), conveys polyubiquitination-mediated signals via TNF receptor associated factor 2 that inhibit apoptosis, while enhancing proliferation and effector functions. CD137 thus behaves as a bona fide inducible costimulatory molecule. These functional properties of CD137 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 123 publications
(148 reference statements)
2
100
0
Order By: Relevance
“…4-1BB is similar to the molecules described above in terms of intrinsic activity (FIG. 3); As with OX40, GITR and CD27, 4-1BB is currently being targeted with receptor agonists to promote antitumour T-cell responses in the context of clinical cancer immunotherapy 122 . However, only a few studies have shown 4-1BB and 4-1BBL involvement in inflammatory disease pathogenesis 5,6,121 .…”
Section: Immune Cell Activationmentioning
confidence: 99%
“…4-1BB is similar to the molecules described above in terms of intrinsic activity (FIG. 3); As with OX40, GITR and CD27, 4-1BB is currently being targeted with receptor agonists to promote antitumour T-cell responses in the context of clinical cancer immunotherapy 122 . However, only a few studies have shown 4-1BB and 4-1BBL involvement in inflammatory disease pathogenesis 5,6,121 .…”
Section: Immune Cell Activationmentioning
confidence: 99%
“…Similar to other TNFRSF members, aggregation of 4-1BB via binding to its ligand results in the recruitment of intracellular TRAF adaptor molecules (TRAF1 and TRAF2), leading to activation of several proinflammatorysignaling pathways (1,5,6). Binding of 4-1BBL to 4-1BB generates strong co-stimulatory signals in T cells that lead to upregulation of anti-apoptotic molecules, cytokine secretion, and enhanced effector function (7,8).…”
mentioning
confidence: 99%
“…CD28 is the canonical T-cell costimulatory molecule expressed at baseline, with functions linked to anabolic metabolism and increased glycolysis, as well as mitochondrial respiration (5). CD137 (4-1BB) is a surface TNFR-family member whose expression is induced on primed T lymphocytes and provides important costimulatory signals (6). Experiments in CD137…”
Section: Introductionmentioning
confidence: 99%